Analytical micro-modeling of masonry periodic unit cells – Elastic properties. (September 2015) - Drougkas, Anastasios; Roca, Pere; Molins, Climent
Highlights: The mechanical properties of masonry composites are derived from PUC calculations. Several different masonry wall and pillar typologies are investigated. The orthotropic elastic characteristics are determined with very low computational cost. The numerical results are compared to experimental data. A parametric investigation is performed to determine the accuracy of the model compared to FE calculations. Abstract: A model for the analysis of masonry periodic unit cells based on detailed micro-modeling principles is presented: an analytical model capable of calculating the orthotropic elastic properties of masonry composites. Several masonry typologies are investigated in the present paper, some of which have received very limited attention, such as Flemish bond walls. The purpose of the model is to achieve the level of detail made possible by the use of detailed micro-modeling techniques while keeping computational costs at a minimum in order to be used as a basis for two-scale modeling of masonry. The results obtained from the described model are compared with experimental data from the existing relevant literature as well as with numerical results obtained from the finite element analysis of masonry periodic unit cells. A parametric investigation is also performed, in which the accuracy of the model is compared against a FE benchmark.